World water and food to 2025: dealing with scarcity - Rosegrant, Mark W.; Cai, Ximing; Cline, Sarah A. (International Food Policy Research Institute, 2002)
Are we headed toward a worldwide water crisis? The increasing demand for water among households, industry, the environment, and especially agriculture is making global water scarcity a perilous possibility.What will happen to food production and global food security as water becomes increasingly scarce? What steps can we take to avert threats to global food supply, the environment, and the livelihoods of those lacking access to clean water? Using state-of-the-art computer modeling to show how water availability and demand are likely to evolve, World Water and Food to 2025 contends that if current water policies continue, so will high levels of food insecurity, environmental degradation, and water-related ill health. Further neglect of water issues could produce a genuine water crisis, which in turn could lead to a food crisis. But we can avoid these outcomes if we make fundamental policy changes now.The authors show exactly which policies and actions could ensure sustainable and efficient water use, enough food for the world’s people, and adequate drinking water for all."-- "About This Book